Molecular Diversity Assessment of PGPR Using Enterobacterial Repetitive Intergeneric Consensus (ERIC) PCR - Shrivastava, Umesh Prasad (Academic Voices: A Multidisciplinary Journal, 2018)
In the present investigation, an attempt has been made to study the diversity of Plant Growth Promoting Rhizobacteria isolated from various rice fields of Indo-Nepal border region. It is reported here that diversity in PGPR of East Champaran, West Champaran and Varanasi district of India and Bara and Parsa district of Nepal showed 76 to 97% similarity among them based on ERIC PCR. Serratia, Agrobacterium, Klebsiella, Pseudomonas etc are predominantly present in the rhizosphere of rice fields of these areas. Protein profile showed that all the isolates were 49-79% similar among each other. The three members consisting species of Klebsiella showed 72% similarity to each other and two species of Agrobacterium showed 80% similarity to each other.